The Importance of Qaul Shahabi in Legal Interpretation - Hanifah, Asma Laili Hanifah; Rizka, Awalia Khalifatur (Ethica: International Journal of Humanities and Social Science Studies, 2024)
The objective of this study is to analyze the contribution of qaul shahabi (the sayings or opinions of the Companions) in the context of Islamic legal interpretation, as well as how qaul shahabi serves as a source of understanding and application of Islamic law. As the direct followers of Prophet Muhammad (peace be upon him), the Companions hold a significant role in the deep understanding of Islamic teachings. The research employs a qualitative approach, utilizing library research methods. The data sources consist of books and various other written materials. This research was conducted through a detailed process of compiling, reading, reviewing, analyzing, and evaluating diverse literature, including the Qur'an, the Sunnah, classical Islamic works, and findings from previous studies. The results of this study show that qaul shahabi not only supports Islamic tradition but also plays a strategic role in establishing the foundations of Islamic law. Their interpretations carry authority because they lived alongside the Prophet Muhammad (peace be upon him) and directly observed his daily practices and teachings. As a result of these observations, it is essential to understand and respect the contributions of the Companions in the context of Islamic law, recognizing that their interpretations were shaped by specific social and historical contexts. Thus, this article enhances a comprehensive understanding of qaul shahabi in the context of Islamic legal interpretation, making it a foundational reference for a more holistic and contextual understanding of Islamic law in the modern era.